Analysis Of Eddy Current Loss Of IPMSM According To The Material Of Permanent Magnet (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In order to reach the performance of the permanent magnet embedded rotor, the choice of magnet is very important. It must be thermally stabilized, and at this point, discussion of eddy current losses is necessary.To proceed with this study, a permanent magnet embedded synchronous motor used in the compressor currently being designed was selected. To derive the eddy current losses in the neodymium-magnets, current density was calculated through the equation. The eddy current loss was mathematically derived using the magnetic conductivity and residual magnetic flux density. Finally, comparative verification was performed through finite element analysis simulation. In this paper, eddy current losses in a N series magnet are mathematically analyzed and we perform comparative verification through simulation using finite element analysis. The Br value indicating the residual magnetic flux density is the lowest in N30 series and the largestin the N48 series. In the case of using the N30 series, the amount of magnetic flux that can be generated is low, so in order to increase the same output, the electric field must be increased by drawing more current from the stator winding. That is, the torque can be further increased. However, since the magnetic flux density experienced by the permanent magnet also increases, eddy current loss that may occur in the  magnet eventually increases. There are also a method of using a split magnet to reduce eddy current losses. Inthe case of a permanent magnet holding a large residual magnetic flux density, the magnets loss is reduced, but there is a disadvantage that the price may be expensive. The losses in the permanent magnet are dissipated as heat. If the eddy current loss increases, the magnet demagnetizes, which in turn leads to a decrease in performance. In the selection of magnets, analysis of losses is essential.